Successful treatments with polymyxin B hemoperfusion and recombinant human thrombomodulin for fulminant Clostridium difficile-associated colitis with septic shock and disseminated intravascular coagulation: a case report - Minami, Kazuhito (Surg Case Rep, 2016)
BACKGROUND: Clostridium difficile (CD)‐associated colitis (CDAC) is endemic and a common nosocomial enteric disease encountered by surgeons in modern hospitals due to prophylactic or therapeutic antibiotic therapies. Currently, the incidence of fulminant CDAC, which readily causes septic shock followed by multiple organ dysfunction syndromes, is increasing. Fulminant CDAC requires surgeons to perform a prompt surgery, such as subtotal colectomy, to remove the septic source. It is known that fulminant CDAC is caused by the shift from an inflammatory response at a local mucosal level to a general systemic inflammatory reaction in which CD toxin-induced mediators’ cascades disseminate. Recently, it has been proven that polymyxin B hemoperfusion (PMX-HP) improves septic shock and recombinant human thrombomodulin (rhTM) controls disseminated intravascular coagulation (DIC). In addition, clinically and basically, it has been shown that these treatments can control serous chemical mediators. Therefore, it is considered that these treatments are promising ones for patients with fulminant CDAC. In the current report, we present that these treatments without surgery contributed to the improvement of sepsis due to fulminant CDAC. CASE PRESENTATION: We encountered a case who developed fulminant CDAC with septic shock and DIC after laparoscopic gastrectomy for gastric cancer. At admission to the intensive care unit, his APACHE II score was 22, which indicated an estimated risk of hospital death of 42.4 %. Our therapies were not the subtotal colectomy to remove septic sources but the combination treatments with both PMX-HP and rhTM. These combination therapies resulted in excellent outcomes, namely the dramatic improvement of septic shock and DIC and the patient’s survival. We speculate that these combination therapies completely inhibit the CD toxin-induced mediators’ cascades and correspond to the removal of septic sources. CONCLUSIONS: We recommend both PMX-HP and rhTM for patients who develop fulminant CDAC with septic shock and DIC to increase the survival benefit and replace the need for surgical treatment.